A study of manufacturing effectiveness on cloud-based manufacturing system - Yoshiteru KATSUMURA; Yuuichi SUGINISHI; Toshiya KAIHARA (Nihon Kikai Gakkai ronbunshu, 2016)
Industrial Internet and Industry 4.0, which refer to the integration of physical industrial machinery with software, internet, along with network sensors, actuators, and other industrial components, are discussed intensively. These technologies provide decantation of manufacturing with cloud-based manufacturing system (CBMS). Since the CBMS enables cross sourcing between connected companies, higher utilization of manufacturing facilities and reduction of manufacturing lead time of products seem to be brought in these companies. As a result, these companies can reduce production cost. We have developed new concept of CBMS which implements dynamical generation of common manufacturing-bill of materials (M-BOM) from engineering-bill of materials (E-BOM). Simulation study on the effectiveness of the CBMS is summarized.